Comparative Study Between Make a Match and Two Stay Two Stray of Cooperative Learning Model on Students’ Learning Outcomes of Hydrocarbon Materials - Weni Tri Sasmi (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: Comparative Study Between Make a Match and Two Stay Two Stray of Cooperative Learning Model on Students’ Learning Outcomes of Hydrocarbon Materials. This study aims to compare the learning outcomes between the Make a Match type and the Two Stay Two Stray type cooperative learning model on hydrocarbon materials. This study carried out at SMK Tamansiswa Kisaran, North Sumatera. The sampling technique used saturated sampling (census), where the samples in consist of 2 class, that is class XII-1 applied the Make a Match and class XII-2 applied the Two Stay Two Stray, with 20 students in each class. Data were collected from pre-test and post-test, then analyzed statistically using t test. Based on the results of data analysis, the average value of learning outcomes in the pretest-posttest in experimental class 1 is 27.5 and 77.0 while the average value of learning outcomes in the pre-post-test in experimental class 2 is 25.3 and 77.8. The t-test was carried out using the independent sample test technique. The significant value (2-tailed) was 0.406˂2.026, meaning that H0 was accepted and Ha was rejected. Based on the results of the study, it can be concluded that there is no significant difference in student learning outcomes who use the Make a Match type with the Two Stay Two Stray type cooperative learning model on hydrocarbon materials.Keywords: Learning model, learning outcomes, make a match, two stay two stray. Abstrak: Studi Perbandingan antara model pembelajaran kooperatif tipe make a match dan tipe two stay two stray terhadap hasil belajar siswa pada materi hidrokarbon. Penelitian ini bertujuan untuk melihat perbandingan hasil belajar antara model pembelajaran kooperatif tipe Make a Match dengan tipe Two Stay Two Stray pada pokok bahasan hidrokarbon. Penelitin ini dilakukan di SMK Tamansiswa Kisaran, Sumatera Utara. Teknik pengambilan sampel menggunakan sampling jenuh (sensus), dimana sampel terdiri dari 2 kelas, yaitu kelas XII-1 menerapkan Make a Match dan kelas XII-2 menerapkan Two Stay Two Stray dengan masing-masing kelas berjumlah 20 siswa. Data dikumpulkan dari pre-tes dan post tes, kemudian di analisis secara statistik menggunakan uji t. Berdasarkan hasil analisis data diperoleh nilai rata-rata hasil belajar kognitif pada pretest-posttest di kelas eksperimen 1 sebesar 27,5 dan 77,0 sedangkan nilai rata-rata hasil belajar kognitif pada pre test-post test di kelas eskperimen 2 sebesar 25,3 dan 77,8. Uji t dilakukan dengan teknik independent sampel test diperoleh nilai signifikan (2-tailed) adalah sebesar 0,406˂2,026, artinya H0 diterima dan Ha ditolak. Berdasarkan hasil penelitian dapat disimpulkan bahwa tidak terdapat perbedaan yang signifikan hasil belajar siswa yang diajarkan dengan model pembelajaran kooperatif tipe Make a Match dengan tipe Two Stay Two Stray pada pokok bahasan hidrokarbon.Kata kunci: hasil belajar, make a match, model pembelajaran, two stay two stray. DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.08